2018
DOI: 10.3892/ijo.2018.4652
|View full text |Cite
|
Sign up to set email alerts
|

High methylation of the 4-aminobutyrate aminotransferase gene predicts a poor prognosis in patients with myelodysplastic syndrome

Abstract: In our previous study, the 4-aminobutyrate aminotransferase (ABAT) gene was screened and selected as a target gene that may affect the prognosis of myelo-dysplastic syndrome (MDS). The present study aimed to determine the prognostic value of ABAT in 152 patients with MDS, 29 patients with acute myeloid leukemia (AML) and 40 controls, by detecting the expression and methylation levels of the ABAT gene. In patients with MDS, the expression levels of ABAT were significantly reduced compared with in the controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In addition to genetic alterations, epigenetic modifications, especially for DNA methylation were also reported to be participated in cancer progression including MDS [24][25][26] . Previous studies almost focused on the single gene change during MDS progression, such as CDKN2B, SOCS1, NR4A2, ABAT, ID4, GPX3, SOX30, and so on [9][10][11][27][28][29][30] . However, few studies demonstrated the whole-genome DNA methylation alterations during MDS progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic alterations, epigenetic modifications, especially for DNA methylation were also reported to be participated in cancer progression including MDS [24][25][26] . Previous studies almost focused on the single gene change during MDS progression, such as CDKN2B, SOCS1, NR4A2, ABAT, ID4, GPX3, SOX30, and so on [9][10][11][27][28][29][30] . However, few studies demonstrated the whole-genome DNA methylation alterations during MDS progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study identified a set of methylated genes (8). One of these genes, 4-aminobutyrate aminotransferase ( ABAT ), was highly methylated and its expression was reduced in MDS patients compared with that noted in healthy controls (8,9). The ABAT gene is localized on chromosome 16p13.2 and encodes a protein responsible for the catabolism of γ-aminobutyric acid ( GABA , an important neurotransmitter in the central nervous system) into succinic semialdehyde (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic alterations, epigenetic modi cations especially in DNA methylation have been shown involved in cancer progression including MDS [24][25][26]. Previous studies almost focused on the single gene change during MDS progression, such as CDKN2B, SOCS1, NR4A2, ABAT, ID4, GPX3, SOX30, and etc [9][10][11][27][28][29][30]. However, little studies showed the whole-genome DNA methylation alterations during MDS progression.…”
Section: Discussionmentioning
confidence: 99%